Measuring Associations Between Physical Activity, Cognitive Ability, and AD‐Vulnerable Brain Networks in Periadolescent Children. (20th December 2022) - Heller, Abi; Phipps, Connor J; Ramirez, Meghan K; Sexton, Jennifer N; Behm, Lillian; Zatkalik, Abigail L; Nickolas, Kristen; Maerlender, Arthur C.; Phatak, Vaishali S; Cramer, Justin A.; Blair, James; Murman, Daniel L; et al.
Abstract: Background: As our population ages, and Alzheimer's Disease (AD) and related pathologies become more prevalent, the need for preventative interventions continues to increase. Physical activity has been investigated as a mechanism to improve memory and other cognitive processes in both healthy and pathological aging. In adults, there is evidence that exercise increases hippocampal volume and strengthens connectivity within functional brain networks such as the Default Mode Network (DMN), Frontoparietal Network (FPN), and Dorsal Attention Network (DAN). These networks support cognitive functions such as spatial working memory (SWM) which involves maintenance and manipulation of visuospatial information; notably, SWM declines as AD progresses. Underlying connectivity in functional brain networks and SWM ability are both influenced by exercise in adults. However, this effect has not been replicated in younger cohorts. The effects of exercise on brain structure and function during periadolsecence, a neurodevelopmental period characterized by expansive changes to functional networks that support cognition, remains unclear. The current study tested associations between resting‐state functional connectivity (rs‐FC) in brain networks, SWM ability, and self‐reported physical activity in a group of periadolescents. Method: Typically‐developing periadolescent children aged 8 – 13 years (N = 60) completed the Cambridge Neuropsychological Test Automated Battery (CANTAB) SWM task, a self‐report physical activity questionnaire, and underwent an MRI of the brain to assess rs‐FC of several functional networks. MRI data were processed using the Human Connectome Project processing pipelines and AFNI software. Result: Analysis of covariance between rs‐FC of the DMN and physical activity suggested greater within‐network connectivity was associated with more minutes of exercise. A similar pattern of within‐network connectivity in the DMN was also observed in association with SWM performance. The DAN and DMN demonstrated greater between‐network connectivity associated with increased physical activity. The FPN displayed a pattern of greater within‐network connectivity associated with SWM performance. Conclusion: Characterizing the influence of physical activity on development of brain networks that support memory may provide key insights on preserving those networks. Understanding these developmental trajectories, and ways to potentially enhance them, could be important for developing interventions to promote brain health by reducing the risk of neurological disease, including late‐life disorders such as AD.